Dokumenty Życia Społecznego z kolekcji Wojewódzkiej i Miejskiej Biblioteki Publicznej im. Cypriana Norwida w Zielonej Górze - wyzwania i potencjały = Documents of Social Life from the Collectionof the Cyprian Norwid Regional and City Public Library in Zielona Góra - Challenges and Potentials - Urbaniak, Agnieszka (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The aim of this study is to draw attention to an extremely interesting type of library resources, namely Documents of Social Life (DŻS). The materials comprising the collection gathered in the Regional and Bibliographic Information Department of the Cyprian Norwid Regional and City Public Library in Zielona Góra constituted the basis for the analyses carried out here. The text characterizes the collection in question with regard to its formal features, shows its specificity resulting from regional references and draws attention to the challenges connected with the library presence of Documents of Social Life. The analyses carried outhere also serve to present the concept created by the author o f this study of the potentials inherent in this type of library collection: informational, aesthetic, co-operative and bonding.
Keywords: biblioteki; Dokumenty życia społecznego; kolekcje; zbiory biblioteczne; potencjały; regionalizm; wyzwania; zasoby biblioteczne; zbiory specjalne; libraries; documents of social life; collections; library collections; potentials; regionalism; challenges; library resources; special collections